Innovative tools to increase Es Cendol production and profit in home industry - Dyah Lestari Yulianti; Ika Nuriyati; Rini Rahayu; Muhammad Agus Salim; Muhammad Mas’ud Chabiburrochman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Cendol drink is a traditional Indonesian beverage made from rice flour and widely consumed in East Java. Many household-scale cendol entrepreneurs are located in Jetis, Mulyoagung Village, Dau District, Malang Regency, where production is still manual and limited to around 3 kg/day. Financial management, production processes, and marketing strategies also remain suboptimal. This community service program aimed to enhance partners’ knowledge and skills in financial management, production techniques, and marketing strategies to improve business performance. The program was implemented through knowledge transfer methods, including counseling sessions, demonstration plots, and mentoring conducted over three months. Program success was measured through improvements in production capacity, product quality, financial management practices, production efficiency, and marketing reach. The results showed that the integration of knowledge transfer and appropriate technology increased production capacity from 3 kg/day to 10 kg/day and raised household entrepreneurs’ profits by approximately 50 percent. The adoption of simple yet applicable technology provided tangible benefits for micro and small enterprises, particularly in improving operational efficiency and business sustainability. This activity also reflected effective collaboration between academia and the community in supporting local economic empowerment. Follow-up programs are recommended to include training in creative content development and social media management, supported by periodic mentoring to ensure sustainable implementation of production and marketing strategies.